2014
DOI: 10.1002/berj.3158
|View full text |Cite
|
Sign up to set email alerts
|

What makes a successful undergraduate? The relationship between student characteristics, degree subject and academic success at university

Abstract: This paper contributes to the empirical evidence on participation and attainment in higher education by reviewing the patterns of entry and success of undergraduate students. It examines the characteristics of entrants to different subjects and considers the role that subject studied plays in determining the likelihood of graduating with a 'good' degree. The data used were drawn from the administrative records of over 38,000 UK-domiciled undergraduate students from one 'elite' British university. Despite consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…[23], [24], [25], and [26]). Previous studies have found that Home students are associated with higher attainment than OS students ( [25], [23] and [24]).…”
Section: Discussionmentioning
confidence: 99%
“…[23], [24], [25], and [26]). Previous studies have found that Home students are associated with higher attainment than OS students ( [25], [23] and [24]).…”
Section: Discussionmentioning
confidence: 99%
“…GPA achieved in high school has been consistently found to be a moderate positive predictor of tertiary academic success (Ackerman et al, 2013;Komarraju & Nadler, 2013;Smith & White, 2015). The findings of the meta analysis by Crisp et al (2014) also show similar results.…”
Section: High School Results and Admission Test Scoresmentioning
confidence: 74%
“…Several factors related to tertiary academic success have been identified in studies including gender (Anderton et al, 2016), self efficacy (Trigwell, Ashwin, & Millan, 2013), high school success (Smith & White, 2015), and less use of internet (Mishra, Draus, Goreva, Leone, & Caputo, 2014). This review paper analyzes these factors within the ecological model presented by Dalton et al (2007).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For reasons of space discussion is limited to patterns across all subjects (an analysis of differences between subjects is presented elsewhere (Smith and White , 2014)). …”
Section: Discussionmentioning
confidence: 99%